Recyclable and Scalable Chemoenzymatic Dynamic Kinetic Resolution of Secondary Alcohols Using Rotating Bed Reactors for Catalyst Compartmentalization - de Almeida, Laiza A. [UNESP]; Löfgren, Erik; Milagre, Cintia D. F. [UNESP]; Milagre, Humberto M. S. [UNESP] (American Chemical Society (ACS), 2024)
In this work, we present the optimizations of the dynamic kinetic resolution of secondary alcohols using a heterogeneous lipase-vanadyl sulfate catalytic system using rotating bed reactors to compartmentalize both catalysts. The reactor design allowed the physical separation of the catalysts, overcoming their mutual incompatibility. Furthermore, the commercial reactors filled with chemical and enzymatic catalysts provided a recyclable and scalable dynamic kinetic resolution (DKR) of secondary benzyl alcohols, achieving up to 5 cycles with high conversions (>90%) and enantiomeric excess (up to >99%) and producing 5.70 g of enantiopure (R)-ester.